Analisis Strategi Pengembangan Bisnis Menggunakan Bisnis Model Kanvas pada Industri Logistik: Studi PT XYZ - Zakaria, Mohammad Arsyi; Alfanur, Farah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research analyzes and formulates the business strategy of PT XYZ using the Business Model Canvas to enhance and innovate in the logistics industry. The focus of the study is to identify logistics challenges, analyze the business model, develop business strategies, and provide policy recommendations to improve PT XYZ's competitiveness and operational efficiency. This research incorporates SWOT, PESTLE, and Porter’s Five Forces analyses in evaluating the nine building blocks of the Business Model Canvas. As a result, 26 strategies were developed, consisting of 9 SO strategies, 4 ST strategies, 6 WO strategies, and 6 WT strategies. Through focus group discussions and member checks, 9 priority strategies were identified and categorized into three approaches: short-term, medium-term, and long-term. The short-term strategies include offering competitive pricing packages, adopting innovative technology, and strengthening relationships with business partners. The medium-term strategies emphasize communication integration through social media and improving service quality. The long-term strategies focus on expanding the partner network and building innovative and sustainable partnerships. The implementation of the nine building blocks in the Business Model Canvas demonstrates PT XYZ's comprehensive adaptation to market dynamics and operational challenges, with the ultimate goal of strengthening its market position and supporting the company's sustainable growth.